Influence of social media usage by salespeople on customer satisfaction in Malaysian B2B environment - Yeo, Eric (2020)
There have been many studies on the use of social media in the B2C context as compared to B2B firms. At the same time, there are not many empirical researches to identify the roles of social media play in B2B, regardless or relationship marketing, buying process, customer satisfaction and or firm performance.